Multiple drug resistant Edwardsiella tarda associated disease outbreak in Labeo catla - A. Uma; S.Ganesh Babu; G. Rebecca (The Indian Veterinary Journal, 2026)
The present study documented an Edwardsiella tarda associated disease outbreak in a Labeo catla commercial fish farm in Tamil Nadu, India. Samples of infected fish (n=10) were collected from the L.catla farm in Thanjavur, Tamil Nadu, India that had reported an outbreak of disease. Bacterial isolation was done from kidney, eye, liver, intestine, brain and gills and the isolates were biochemically characterized, confirmed by PCR amplification and nucleotide sequencing as E.tarda (E4L/SRLAAH/2020). Antibiogram showed that the isolate was either resistant or intermediately resistant to Chloramphenicol, Ampicillin, Oxytetracycline, Cefotaxime, Vancomycin, Amoxicllin, Erythromycin, Ceftazidime, Kanamycin and Tetracycline and sensitive to five antibiotics viz., Norfloxacin, Ciprofloxacin, Nalidixic acid, Oflaxacin and Co-trimazole.